Probabilistic explanation for episodic ecological events - Husile Bai; Olivia Mondlock; Courtenay Strong; Jalene M LaMontagne; Benjamin Zuckerberg (Environmental Research Letters, 2024)
Climate associated ecological phenomena that occur approximately once per decade suggest the influence of decadal climate oscillations. However, the consistency and origins of such climate patterns in the Atlantic and Pacific regions is currently under debate. Here, we propose a probabilistic explanation for episodic ecological events based on the likelihood of multiple climate patterns converging in a particular phase combination. To illustrate, we apply this model to continental scale facultative migration of seed-eating finches out of the boreal forest. This irruption phenomenon is triggered by seed crop failures stemming from two weakly correlated climate patterns occurring simultaneously in their positive phases—the North Atlantic Oscillation (NAO) and the North Pacific Oscillation (NPO). The joint probability of NAO and NPO both being positive (above upper tercile) is about $(1/3)^2≈ 0.11$ , illustrating a simple probabilistic explanation for quasi-decadal finch irruption and potentially other episodic ecological events in regions affected by multiple climate modes.